Turntable technique the art of the DJ - Webber, Stephen W. (Berklee Press, 2009)
The text and sound discs provide step-by-step instructions for using the turntable as a musical instrument. The text includes photographs, musical exercises, and a history of DJing and hip-hop culture
"Production: turntable technique"--Cover. - Includes index. - The two sound discs have identical contents. - "HL50449482"--Cover
Text: Part I, playing the turntables -- Part II, interviews
Sound discs: Side 1. One! : (110.4 bpm funk jam) ; White hot noise : (perfect to start scratching with) -- Side 2. Entrancing miles : (110.4 bpm techno-trance groove) ; Skipless scratch samples : (repeated shorter samples to cut with)
Keywords: Turntablism / Methods; Turntablists / Interviews; Plattenspieler; Discjockey; Musikinstrument; Einführung